2015
DOI: 10.4103/0971-4065.151358
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and graft dysfunction among kidney transplant recipients: Increased risk for atherosclerosis

Abstract: Weight gain after kidney transplant is common, and may be related to graft dysfunction and high cardiovascular risk. We investigated the prevalence of obesity and evaluated the relationship between obesity and graft dysfunction in kidney transplant recipients (KTRs). All patients who received kidney transplant at the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) between January 2005 and December 2009 were recruited. Information on demographics, clinical characteristics and post-transplant care were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Acknowledging the limitation of the small number of patients and length of the follow-up, we did not notice significant differences in those parameters. In contrast, Aminu et al have reported that obese patients post-renal transplantation were more prone to graft dysfunction and progression of atherosclerosis, including higher mean arterial blood pressure, total cholesterol, triglycerides, left ventricular mass index, and higher carotid intima-media thickness [ 24 ]. This could be explained by the fact that the mean duration of follow-up in the Aminu et al study was 60 ± 18.8 (range 36–89) months while it was 12 months in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Acknowledging the limitation of the small number of patients and length of the follow-up, we did not notice significant differences in those parameters. In contrast, Aminu et al have reported that obese patients post-renal transplantation were more prone to graft dysfunction and progression of atherosclerosis, including higher mean arterial blood pressure, total cholesterol, triglycerides, left ventricular mass index, and higher carotid intima-media thickness [ 24 ]. This could be explained by the fact that the mean duration of follow-up in the Aminu et al study was 60 ± 18.8 (range 36–89) months while it was 12 months in our study.…”
Section: Discussionmentioning
confidence: 99%
“…KTx recipients represent a whole spectrum of undernutrition and obesity. While a higher BMI is rarely related to adverse outcomes in HD patients [ 12 ], it appears disadvantageous in KTx patients [ 13 ]. In the perioperative period, obesity is associated with poor wound healing, prolonged hospitalization, and surgical complications including lymphoceles and delayed graft function [ 14 ].…”
Section: Bmi In Ktx Recipientsmentioning
confidence: 99%
“…In the perioperative period, obesity is associated with poor wound healing, prolonged hospitalization, and surgical complications including lymphoceles and delayed graft function [ 14 ]. In the late post-transplant period, obese individuals are more prone to impaired graft function, the presence of proteinuria, PTDM, and atherosclerosis progression, which lead to hypertension and CV complications [ 13 ]. The largest increase in body mass occurs within the first 12 months following transplantation [ 15 ].…”
Section: Bmi In Ktx Recipientsmentioning
confidence: 99%